Effect of Calcium Carbonate Addition on The Growth and Feed Conversion Ratio of Gourami (Osphronemus goramy) Seed - Dewi Nur'aeni Setyowati; Anita Prihatini Ilyas; Awan Dermawan; Sanca Rahmatullah (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2022)
Gourami is one of the main freshwater fish commodities which has a high economic value. One of the efforts that can be made to increase the productivity of gourami is the provision of macromineral in the form of calcium carbonate (CaCo3). This study aimed to determine the effect of calcium on productivity that would be seen through the growth rate and feed conversion ratio of gourami seed. The study consisted of five doses of calcium carbonate, each of which was repeated three times. As for treating the doses of calcium carbonate, including 1 (0 mg / L CaCO3), 2 (150 mg / L CaCO3), 3 (200 mg / L CaCO3), 4 (250 mg / L) CaCO3) and 5 (300 mg / L CaCO3). The maintenance medium is added with a salinity of 3 ppt in order to save metabolic energy through an osmoregulation mechanism so that the available energy is expected to be used to increase growth. The result or absolute weight growth was not significantly different based on the analysis of variance and linier regression analysis. The analysis of variance showed that no significant different for survival rate of all treatments. The value of feedÃÂ conversion ratio was not significantly different based on analysis of variance and linier regression analysis. Addition of calcium carbonate did not give significant difference in the absolute weight growth, survival rate, and feed conversion ratio of gourami seed.